Thermographic Investigation of Osseous Stress Pathology - Khan, Masood Mehmood; Arthur, Daniel; Barclay, L. (IEEE-EMBC, 2011)
The debilitating pathology of stress fracture accounts for 10% of all athletic injuries[2], with prevalence as high as 20% in modern military basic training cohorts [3]. Increasing concerns surrounding adverse effects of radiology [5],combined with the 12.5% contribution of diagnostic imaging to Australian Medicare benefits paid in 2009-10 [6], have prompted the search for alternative/adjunct electronic decision support systems[7]. Within conducive physioanatomic milieu, thermal infrared imaging (TIRI) may feasibly be used to remotely detect and topographically map diagnostically useful signs of suprathreshold thermodynamic pathophysiology. This paper details a three month clinical pilot study into TIRI-based detection of osseous stress pathology in the lower legs of Australian Army basic trainees. A dataset of over 500 TIRI’s was amassed. The apparent ‘normal’ thermal profile of the anterior aspect of the asymptomatic lower leg is topographically defined and validated against current thermophysiological theory [8] via cadaveric dissection.